Celeridade processual e concretização dos direitos fundamentais sociais nos juizados especiais federais - Borges, Tarcísio Barros (2009)
This work analyses two juridical questions that are strongly related: the issue of social rights efficacy and the matter of procedure. celerity when related with them. In the beginning, the study examined how the fundamental rights was born in the juridical western societies e how they developed to became one of the most substantial attributes of contemporary constitutional democracies. It was affirmed in the text that 1988 Brazilian Federal Constitution fully adopted the profile of Social State, as happened in Western Europe after the Second World War finished in 1945. In that time and after, new constitutional doctrines passed to consider the Constitution as a arder of values directed to satisfy human dignity, what have taken the State to act more efficiently in favor of equality among mankind, by the recognition of state social duties. Lastly, the study analyzed if the Brazilian federal small claims courts are suitable to observe the right to procedure celerity, which is laid in Brazilian Constitution. The conclusion was that, after the study of the laws that regulate the federal small claims and from the view of statistics, the legal changes adopted by Federal Law 10.259/2001 admitted major celerity in law suits concerning to social rights